Evaluation of (Ba 0.5Sr 0.5) 0.85Gd 0.15Co 0.8Fe 0.2O 3-[delta] cathode for intermediate temperature solid oxide fuel cell - Li, Z.; Wei, Bo; Lu, Z.; Zhang, Y.; Chen, Kongfa; Miao, J.; Su, W. (Elsevier Science Ltd, 2012)
A perovskite-type (Ba0.5Sr0.5)0.85Gd0.15Co0.8Fe0.2O3−δ (BSGCF) oxide has been investigated as the cathode of intermediate temperature solid oxide fuel cells (IT-SOFCs). Coulometric titration, thermogravimetry analysis, thermal expansion and four-probe DC resistance measurements indicate that the introduction of Gd3+ ions into the A-site of Ba0.5Sr0.5Co0.8Fe0.2O3−δ (BSCF) leads to the increase in both oxygen nonstoichiometry at room temperature and electrical conductivity. For example, the conductivity of BSGCF is 148 S cm−1 at 507 °C, over 4 times as large as that of BSCF. Furthermore, the electrochemical activity toward the oxygen reduction reaction is also enhanced by the Gd doping. Impedance spectra conducted on symmetrical half cells show that the interfacial polarization resistance of the BSGCF cathode is 0.171 Ω cm2 at 600 °C, smaller than 0.297 Ω cm2 of the BSCF cathode. A Ni/Sm0.2Ce0.8O1.9 anode-supported single cell based on the BSGCF cathode exhibits a peak power density of 551 mW cm−2 at 600 °C.